2017
DOI: 10.1007/s00467-017-3736-y
|View full text |Cite
|
Sign up to set email alerts
|

HUS-induced cardiac and circulatory failure is reversible using cardiopulmonary bypass as rescue

Abstract: Fatal outcome in patients with HUS may be the result of severe cardiac involvement. The present case illustrates the need for intensive supportive care, including the use of CPB, as the cardiac symptoms in HUS patients may be reversible. We suggest the monitoring of cardiac-specific enzymes, ECG and echocardiography in high-risk patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…These pathologies might cause occluded vessels and, subsequently, ischemia. 2,5 Congestive heart failure, hypertension, pericardial effusion, myocarditis, arrhythmias, depressed myocardial function, and left ventricular hypertrophy are the most prevalently seen heart involvements in STEC-HUS patients. 7,8 The underlying mechanisms in HUS cases who have arrhythmias are microthrombi, microaneurysms, and hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These pathologies might cause occluded vessels and, subsequently, ischemia. 2,5 Congestive heart failure, hypertension, pericardial effusion, myocarditis, arrhythmias, depressed myocardial function, and left ventricular hypertrophy are the most prevalently seen heart involvements in STEC-HUS patients. 7,8 The underlying mechanisms in HUS cases who have arrhythmias are microthrombi, microaneurysms, and hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…1 This condition manifests with bloody diarrhea that is caused by an infection with STEC. 2 Gastrointestinal, neurological, pancreatic, hepatic, and cardiac dysfunction are extrarenal manifestations of STEC-HUS. The estimated mortality due to STEC-HUS is up to 5%, and that is primarily attributed to complications related to the central nervous system and cardiovascular system.…”
Section: Introductionmentioning
confidence: 99%
“…TMA of the coronary vessels is the main underlying histopathological finding, and it leads to myocardial ischemia/infarction/dysfunction, myocarditis, congestive heart failure, arrhythmias, and pericardial effusion/tamponade. [2][3][4][5][6] Histopathologically proven, myocarditis has also been reported in association with HUS. 6,7 Abu-Arafeh et al 6 reported a case of a 13-year-old adolescent with HUS and documented E. coli O157:H7 who had sudden cardiac arrest and subsequently died due to the development of hypotension, bradycardia, and ventricular arrhythmias.…”
Section: Discussionmentioning
confidence: 99%
“…The successful use of ECMO in HUS-associated refractory cardiogenic shock has been reported in three paediatric patients with STEC-HUS. [3][4][5] Of note all had mechanical support established (two on ECMO and one on cardiopulmonary bypass) subsequent to cardiac arrest; however, all progressed to cardiac recovery allowing decannulation after 7-10 days. None received Eculizumab.…”
Section: Discussionmentioning
confidence: 99%
“…2 Case series in children with STEC-HUS have raised the potential role of extra-corporeal support in those with cardiac involvement, and of Eculizumab in those with neurological involvement. [3][4][5][6][7] Herein, we present, to our knowledge, the first adult patient with cardiogenic shock and evidence of neurological involvement secondary to STEC-HUS successfully supported with extracorporeal membrane oxygenation (ECMO) and Eculizumab. A 19-year-old female with no medical history presented to a district general hospital with bloody diarrhoea.…”
Section: Introductionmentioning
confidence: 99%